2013
DOI: 10.1007/s00259-013-2425-8
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion SPECT in patients with suspected pulmonary embolism

Abstract: Purpose Ventilation/perfusion tomography (V/P SPECT ), with new interpretation criteria and newer tracers for ventilation imaging, has markedly improved the diagnostic yield in acute pulmonary embolism (PE). Here, we evaluated the diagnostic performance of perfusion SPECT (P SPECT ) without ventilation imaging. Methods We studied 152 patients with clinically suspected PE who had been examined with both V/P SPECT and multidetector computed tomographic angiography (MD-CTA). The diagnosis or exclusion of PE was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Perfusion SPECT is only recommended in emergencies when the diagnosis of PE would otherwise be missed as pointed out in a recent article and editorial [11,12].…”
Section: Perfusion Spectmentioning
confidence: 99%
“…Perfusion SPECT is only recommended in emergencies when the diagnosis of PE would otherwise be missed as pointed out in a recent article and editorial [11,12].…”
Section: Perfusion Spectmentioning
confidence: 99%
“…Bajc et al suggested that perfusion SPECT (without ventilation SPECT) might be a valid alternative to V/Q SPECT or multidetector CT angiography in critically ill patients [36]. Its sensitivity was 53 out of 59 (90 %) and its specificity was 88 out of 93 (95 %).…”
Section: Perfusion Spect Accuracymentioning
confidence: 99%
“…The specificity ranged from 71 to 100 % [21,22,24,[26][27][28][29][30][31][32][33][34][35][36] except in a single investigation of six patients without PE, in which the specificity was 0 out of 6 (0 %) [25]. The agents used for V SPECT differed (Table 1) and the diagnostic criteria for interpretation of SPECT also differed among investigations (Table 1).…”
Section: Non-diagnosticmentioning
confidence: 99%
See 2 more Smart Citations